CARTOGRAFIAS DO PODER EM PROCESSOS CRIMINAIS (COMARCA DE MALLET – PR, 1950-1970) - Franco, Júlio César (2019)
This dissertation aims to compose a cartography of the power relations from the criminal processes of the Comarca de Mallet between 1950 and 1970. This cartography, seeks to understand the power relations in the productions of truths, subjects and knowledge within a space-time clipping specific. In the dialogue with post structuralism, we investigate the criminal processes and the mechanisms that make up the legal apparatus. We rely on the concepts of devices and diagrams on which Foucault dealt primarily in the Discipline and Punish, and with the concepts of abstract machines and concrete assemblages that Deleuze formulated with Guattari in A Thousand Plateaus. Thus, diagrams and devices, abstract machines, and concrete assemblages compose the elements of a cartographic investigation of power relations. In analyzing the processes produced by the Comarca, an investment of power over spaces was evidenced, especially when there are violence. Visibility and looks change, as well as the control mechanisms of such spaces. In the period we select, we find that homicide records decline and sex crimes increase, which does not necessarily mean that there were more or less crimes in previous decades. Our hypothesis is that there were changes in the punitive apparatus of control and vigilance as well as a change in the notions of crime and violence that in tension with legal norms and moral precepts produced truths, incited knowledge and raised subjects. In the relations with the subjects, it was evidenced that certain moral and social values were reproduced in the quotidian. When observed in the judiciary, these values become tools of truth production, which goes against the precepts of the Brazilian Penal Code of 1940 that had substantially reduced moral judgments about the crime and the criminal. What was possible to understand from the criminal processes is that the practice of justice is not external to society, thus demonstrating a judicial apparatus as a reflection of that region, even if almost opaque and sometimes distorted.